Comparing Socio – Economic Statue, Sensation - Seeking And Personality Traits Of Addicts And Nonaddicts In The City Of Izeh - Orak, Jahanbakhsh (The Turkish Online Journal of Design Art and Communication, 2016)
The aim of this study is to evaluate the socio-economic and personality factors and sensation-seeking and drug addiction in the Ize city. The sample is consisted of 18 individuals that were divided on the basis of drug addiction and normal in both groups (9 people with addiction and 9 normal people). This is a causal-comparative study. The research tool was a questionnaire MMPI short form questionnaire and Zuckerman Sensation Seeking Scale. Hypotheses include: 1. Between psychological and personality characteristics (hypochondriasis, depression, hysteria, psychopathy, paranoia, mental weakness, schizophrenia and Hypomania) in addicted and normal people, there is a significant difference. 2. Between sensation seeking of addicted and normal people, there is a significant difference. 3. Between socio-economic status of addicted and normal people, there is a significant difference. To test the hypotheses of t test, independent groups were used. The study results showed that between psychological characteristics of addicted and normal people, there is a significant difference in the level of p <5 %.
Keywords: Socio Economic Status; Personality Traits; Sensation Seeking; Addicted; Izeh; Bağımlı; Sosyo Ekonomik Durum; Kişilik Özellikleri; Duyum; İzeh